A short-term comparison between the effect of two different concentrations of methotrexate on ovarian tissues and function of female albino rats - Hussein, Alak; Ali, Samara M. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: methotrexate is an antifolate that is widely used in cancers and inflammatory or auto- immune diseases, it is also known to be contraindicated in pregnancy, breast feeding and not recommended in patients planning to be parents since it has a harmful effect on fetus and gonads.Ovarian function can be evaluated by certain parameters like the levels of female hormones or anti- Mullerian hormone which is considered as a good indicator for this purpose or histopathological examination of ovarian follicles especially the primordial follicles.  Objective: the aim of this study is to determine the effect of two different concentrations of methotrexate on ovarian tissue integrity and function.  Materials and method: adult female albino rats (n=30) were randomly divided in to 3 groups; group A (n=10) in which animals were treated with i. p injection of normal saline once weekly for four weeks, group B (n=10) in which animals were treated with i. p. injection of 1mg/ kg bw of methotrexate once weekly for four weeks, and lastly group C in which animals were treated with i. p. injection of 2.5 mg/ kg bw of methotrexate once weekly for four weeks. Then serum level of anti- Mullerian hormone were measured and histopathological examination of the ovaries were done to evaluate ovarian injury caused by methotrexate treatment.Results: this study has demonstrated that methotrexate in the both 1mg and 2.5 mg / kg of BW doses did not significantly reduce the levels of anti- Mullerian hormone and the number of primordial follicles and atretic follicles were also not significantly affected by the treatment of methotrexate in both doses. While histopathological examination revealed mild ovarian damage in case of treatment with 1mg/ kg bw of methotrexate and moderate damage in case of treatment with 2.5 mg/ kg bw of methotrexate. Conclusions: there is no important difference between the effects of 1 and 2.5 mg/ kg of BW of methotrexate on ovarian function but there is a slight difference in the effects of the two different doses on the integrity of ovarian tissue.